Preliminary Petromagnetic Study of 1849, 1926, 1963, 1968 and 1974 Surface Lavas from Batur Volcano, Bali, Indonesia: Insight on the Magmatic Process of Source and Rock Magnetic Nature (Rudarsko-geološko-naftni zbornik, 2023)
Geochemical and petrographic characterizations were carried out on five episodic effusive eruptions from Batur Volcano on the Island of Bali, Indonesia, and revealed that these lavas are basaltic to andesitic in composition. Various micro-textures were identified, reflecting pre-eruptive magmatic processes, magma mixing, and adiabatic decompression. Apart from XRF analyses, the five lava flows (L849, L926, L963, L968 and L974) were subjected to magnetic analyses in the form of magnetic susceptibility and magnetic hysteresis measurements. The presence of cyclicity in the magmatic process is suggested by the variation of micro-texture types, CaO content, and magnetic susceptibility values. Two possible models of this cyclicity are presented. In the first model, cyclicity is driven by the variation of influx from the lower magma chamber that affects the interaction of magma with the surrounding rocks. In the second model, cyclicity is affected by the appearance of a new magmatic vent, which causes intense interaction with surrounding rocks. This study infers that combined micro-texture, composition, and magnetic susceptibility analyses might provide insight into the cyclicity of lava episodes observed in active volcanos such as Batur.